POMOCY!!!
1.Rozwiąż równania.
a)5x+3=x+19
b)2+3m=5-5m
c)1,2-1,9x=0,5(x+3)-0,3(x+5)
d)4(x+3)=5x-19

2.Uzupełnij.
a_3(x-4)=3x-....
b)5(2+4x)=....+20x
c)2(5a+7b-3)=10....+14....-....
d)-(3r-5t)=-3r....5t
e)-3/4(8x+12y)=-6....-....
f)-(-7a+9b)=....a-....b
g)2,5(-4p-10q)=-10....-25....
h)-1/2(6a+8)=....-4

3.Wykonaj działania.
b)(16z-2)*3/4=
c)-0,5(8x+12y-6)=
d)-(p+r)*4=
e)2n(k+m)=
f)a(c-b+3)=
g)-3s(-2s-t-1/3)=
h)jeden i jedna trzecia x(0,75+3x)=

3

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-25T15:15:50+01:00
1.
a) 5x+3=x+19
5x-x = 19-3
4x = 16 /: 4
x = 4
b) 2+3m=5-5m
3m+5m = 5-2
8m = 3 /: 8
m =
c) 1,2-1,9x=0,5(x+3)-0,3(x+5)
1,2-1,9x = 0,5x + 1,5 - 0,3x + 1,5
- 1,9 x - 0,5 x + 0,3x = 1,5 + 1,5 - 1,2
-2,1 x = 1,8 /: ( - 2,1 )
x =
d) 4(x+3)=5x-19
4x+12= 5x - 19
4x - 5x = -19-12
-x = -31 /: -1
2.
a) 3(x-4)=3x-12
b)5(2+4x)=10+20x
c)2(5a+7b-3)=10a+14b-6
d)-(3r-5t)=-3r+5t

2010-02-25T15:17:46+01:00
A)5x+3=x+19
5x-x=19-3
4x=16/:4
x=4
b)2+3m=5-5m
3m+5m=5-2
8m=3/:8
m=3/8 to ułamek
c)1,2-1,9x=0,5(x+3)-0,3(x+5)
1,2-1,9x=0,5x+1,5-0,3x-1,5
-1,9x-0,5x+0,3x=1,5-1,5-1,2
1,7x=-1,2/:1,7
x≈-0,705
d)4(x+3)=5x-19
4x+12=5x-19
4x-5x=-19-12
-x=-31/*(-1)
x=31
2.
a)3(x-4)=3x-12
b)5(2+4x)=10+20x
c)2(5a+7b-3)=10a+14b-6
d)-(3r-5t)=-3r + 5t
e)-3/4(8x+12y)=-6x-9y
f)-(-7a+9b)=7a-9b
g)2,5(-4p-10q)=-10p-25q
h)-1/2(6a+8)=-3a-4

3.
b)(16z-2)*3/4=12z-1,5
c)-0,5(8x+12y-6)=-4x-6y+3
d)-(p+r)*4=-(4p+4r)=-4p-4r
e)2n(k+m)=2nk+2nm
f)a(c-b+3)=ac-ab+3a
g)-3s(-2s-t-1/3)=6s+3st+1s
nie wiem czy ten x słuzy za razy czy to po prostu x wiec obliczyłam dwa razy te rownanie
h)jeden i jedna trzecia *(0,75+3x)=4/3*(0,75+3x)=1+4x
h)jeden i jedna trzecia x(0,75+3x)=4/3x*(0,75+3x)=
=1x+4x²
:))
1 5 1
2010-02-25T15:54:01+01:00
1
a)
5x+3=x+19
5x-x=-3+19
4x=16/÷4
x=4

b)
2+3m=5-5m
3m+5m=-2+5
8m=3/÷8
m=3/8

c)
1.2-1.9x+0.5(x+3)-0.3(x+5)
1.2-1.9x=0.5x+1.5-0.3x-1.5
-1.9x-0.5x=0.3x=-1.2+1.5-1.5
-2.1x=-1.2/-2.1
x=0.5

d)
4(x+3)=5x-19
4x+12=5x-19
4x-5x=-12-19
-x=-31/÷(-1)
x=31

2.
a) 3(x-4)=3x-4
b)5(2+4x)=10+20x
c)2(5a+7b-3)=10a+14b-6
d)-(3r-5t)=-3r+5t
e) -3/4(8x+12y)=6x-9y
f)-(-7a=9b)=7a-9b
g)2.5(-4p-10q)=-10p-25q
h)-1/2(6a+8)=-3a-4

3
b)(16z-2)×3/4=54/4z-6/4
c)-0.5(8x+12y-6)=-4x-6y+3
d)-(p+r)×4=-p-r×4
e)2n(k+m)=2nk+2nm
f)a(c-b+3)=ac-ab+3a
g)-3s(-2s-t-1/3)6s²+3st+s
h)1.1/3x(0.75+3x)=4/3x(3/4+3x)=12/12x+3x=x+3x=4x